Biosynthesis of Long Chain Polyunsaturated Fatty Acids in the Marine Ichthyosporean Sphaeroforma arctica. Issue 3 (13th December 2012) - Vrinten, Patricia; Mavraganis, Ioannis; Qiu, Xiao; Senger, Toralf
Abstract: Sphaeroforma arctica is a unique, recently discovered marine protist belonging to a group falling close to the yeast/animal border. S. arctica is found in cold environments, and accordingly has a fatty acid composition containing a high proportion of very long chain polyunsaturated fatty acids, including the ω3 polyunsaturated fatty acids eicosapentaenoic acid (EPA) and docosahexanoic acid (DHA). Two elongases and five desaturases, representing the complete set of enzymes necessary for the synthesis of DHA from oleic acid, were isolated from this species and characterized in yeast. One elongase showed high conversion rates on a wide range of 18 and 20 carbon substrates, and was capable of sequential elongation reactions. The second elongase had a strong preference for the 20‐carbon fatty acids EPA and arachidonic acid, with over 80 % of EPA converted to docosapentaenoic acid (DPA) in the heterologous yeast host. The isolation of a Δ8‐desaturase, along with the detection of eicosadienoic acid in S. arctica cultures indicated that this species uses the alternate Δ8‐pathway for the synthesis of long‐chain polyunsaturated fatty acids. S. arctica also carried a Δ4‐desaturase that proved to be very active in the production of DHA from DPA. Finally, a long chain acyl‐CoA synthetase from S. arctica improved DHA uptake in the heterologous yeast host and led to an improvement in desaturation and elongation efficiencies.